Business Development Strategies Using SWOT Analysis in the Cahaya Modern Home Industry - Deby Riska Sonia; Arwin Sanjaya; Marnala Joshua Hutajulu (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2020)
The purpose of this study is to determine the internal conditions (Strengths, Weaknesses) and external (Opportunities, Threats) of Cahaya Modern SMEs using SWOT, so it can be identified which strategies can be used for business development. The type of research used is kualitatif. The conclusion of this research is there are strength and weakness factors that influence the internal conditions of Cahaya Modern SMEs. Those are the workers that live nearby the business location and sales promotion that are still offline. The opportunities and threat factors that influence external conditions are fostered by the government and the existence of substitute products. Based on the calculation of IE Cahaya Modern SMEs matrix lies in quadrant II which means Grow and Build. There are alternative business development strategies obtained from data processing using QSPM. First is making alternative products using additional raw materials, incorporating technological sophistication in producing products, maintaining quality and showing excellence, adjusting consumer demand, optimizing marketing, being active in government activities, and utilizing technological advancements as an act of promotion. The main priority result of the analysis is to make alternative products using additional raw materials with a TAS of 5.62.